Four-wheel independent brake control to limit tire slip under unknown road conditions. (July 2018) - Joa, Eunhyek; Yi, Kyongsu; Sohn, Kimo; Bae, Hyungjune
Abstract: This paper presents a four-wheel independent brake control method for vehicle stability under various road conditions without any tire–road friction information. For safety reasons, it is important to guarantee vehicle stability under unknown road conditions. The proposed algorithm is based on analysis of vehicle dynamic behavior on a tire slip force plane, and consists of three parts, Lateral stability decision, Desired motion governor, and Brake allocation. Lateral stability decision identifies whether vehicle is stable or unstable based on 'Peak slip line'. The desired motion governor determines both target yaw moment and deceleration to stabilize the vehicle. The brake allocation decides brake inputs of four wheels to achieve desired motions. The proposed algorithm has been evaluated via both computer simulations and vehicle tests. The performance evaluation has been conducted on dry asphalt and wet pebble road using E-segment car. It has been shown via both computer simulations and vehicle tests that the proposed algorithm can successfully maintain the vehicle stability under various road conditions. The performance of the proposed algorithm has been compared to previously developed reference yaw rate and side slip angle tracking algorithm at simulation level and built-in Electronic Stability Control(ESC) logic in the vehicle tests. It has been also shown that the proposed control law provides improved performance compared to others.